Kualitas Pelayanan Sebagai Pembentuk Kepuasan Pelanggan di Industri Restoran - Thania Frisca Wardhani; Waluyo Budi Atmoko; Sugiyarmasto Sugiyarmasto; Yulianto Yulianto (Jurnal Bisnis dan Kewirausahaan, 2024)
Abstract This study aims to examine a customer satisfaction model. Customer satisfaction is hypothesized to be influenced by service quality, while service quality is affected by customer orientation. Customer orientation is influenced by both job satisfaction and work motivation. Furthermore, job satisfaction is expected to be influenced by work motivation, and work motivation is also proposed to have a direct effect on customer orientation. The data were collected through questionnaires distributed to customers and employees of Rocket Chicken restaurants in Surakarta, Indonesia. Purposive sampling was employed to select the respondents, comprising 40 employees and 100 customers. The hypotheses were tested using simple regression analysis. The findings indicate that work motivation has no significant effect on either job satisfaction or customer orientation. In addition, job satisfaction does not have a significant effect on customer orientation, and customer orientation does not significantly influence service quality. However, service quality has a significant positive effect on customer satisfaction.